(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Many higher education institutions (HEIs) have implemented information and communication technology (ICT) in their management processes. One of the implementation is used in academic affair management usually called academic information system (AIS). Some of the institutions also have implemented Education 3.0 paradigm in their learning processes. However, most of the existing AIS was only used for the administrative purpose and only support users from the internal of the institutions. In the other way, the characteristics of Education 3.0 are consisting of learning and administration processes and also support involvement from parents and industry. This study will use SistemInformasiAkademikUniversitasLanglangbuana (SIAk UNLA) in Bandung, Indonesia as a case study and analysis the gaps between existing AIS and the characteristics of Education 3.0 paradigm. The results are recommendation functionalities to be added to AIS in the case for supporting Education 3.0 paradigm.